“My Concerns Were Unproven”: A Phenomenological Study on Tolerance Experiences of Non-Muslim Students at Muhammadiyah University - Suyatno, Suyatno; Sayuti, Muhammad; Rahmatika, Nuniek; Hartanto , Dody; Wu , Febiana Kornelia; Samaalee, Abdunrorma (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Muhammadiyah University (PTM), as an educational institution with a distinct ideological mission, frequently admits non-Muslim students. This phenomenon theoretically creates a quo-vadis scenario, and the primary objective of the university is to instill the ideology of association in students. However, there is an interest for Muhammadiyah to emphasize its position as a moderate organization that upholds religious tolerance. Therefore, this study aimed to investigate the experiences of non-Muslim students at Muhammadiyah University in Yogyakarta, particularly in terms of religious tolerance. This study used a qualitative with a phenomenological method. In-depth interviews were conducted with 7 non-Muslim students who had completed studies at Muhammadiyah University in Yogyakarta. Subsequently, data were analyzed using interpretative phenomenological analysis. The results showed that non-Muslim students experienced tolerance when studying. Based on the report, initial concerns were unproven, as students felt comfortable with differences, worshiped according to beliefs, and were free from discrimination. Moreover, Muhammadiyah University provided a platform for interfaith dialogue, facilitating a shift from mere tolerance theology to active engagement. The results showed the significant role of Muhammadiyah University in fostering tolerance education for non-Muslim students.